1988
DOI: 10.1084/jem.167.2.570
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages secrete a novel heparin-binding protein with inflammatory and neutrophil chemokinetic properties.

Abstract: We report the identification and purification of a new inflammatory monokine synthesized by the macrophage tumor cell line RAW 264.7 in response to endotoxin. This monokine, which we term "macrophage inflammatory protein" (MIP), is a doublet with an apparent molecular mass of approximately 8,000 daltons on SDS-PAGE but forms aggregates of greater than 2 x 10(6) daltons as assessed by gel filtration. Partial NH2-terminal amino acid sequence data reveal no significant homology with any previously described prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
239
1
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 530 publications
(255 citation statements)
references
References 23 publications
14
239
1
1
Order By: Relevance
“…MIP-1α was originally identified as a product of endotoxin stimulated RAW264.7 macrophages [14,15]. It has been shown that MIP-1α contributes to lung leukocyte accumulation and acute lung injury in various animal models [16,17]. As shown in Figure 5, MIP-1α was increased by 40% following hyperoxic exposure (P<0.05).…”
Section: Overexpression Of Mnsod Decreases Hyperoxia-induced Mip-1α Ementioning
confidence: 71%
“…MIP-1α was originally identified as a product of endotoxin stimulated RAW264.7 macrophages [14,15]. It has been shown that MIP-1α contributes to lung leukocyte accumulation and acute lung injury in various animal models [16,17]. As shown in Figure 5, MIP-1α was increased by 40% following hyperoxic exposure (P<0.05).…”
Section: Overexpression Of Mnsod Decreases Hyperoxia-induced Mip-1α Ementioning
confidence: 71%
“…In rodents, CCL2 has been shown to contribute to insulin resistance (16,34) and to adipocyte dedifferentiation (34). CCL3 is a monokine produced by macrophages and involved in inflammation, acting as a chemoattractant and an activator of polymorphonuclear leukocytes (44). TNF-␣ is a proinflammatory and lipolytic cytokine overexpressed in obesity by tissue macrophages and able of inducing insulin resistance, at least in rodents and human cells in vitro (33).…”
Section: Discussionmentioning
confidence: 99%
“…Other known macrophage-derived growth factors differ from MD-HBGF in that either they do not bind to heparin, e.g., TGF-f, TGF-a, TNF-a ( Figure 5); they are endothelial cell mitogens, e.g., TGF-a (Schreiber et al, 1986); or they are endothelial cell inhibitors (TGF-3, TNF-a) (Baird and Durkin, 1986;Heimark et al, 1986;Frater-Schroder et aL., 1987;Muller et aL, 1987;Schweigerer et aL, 1987). The macrophage inflammatory proteins (MIP), although heparin-binding, are low molecular weight (8 kDa) anionic polypeptides that are pyrogenic and chemotactic for leukocytes but do not appear to be mitogenic (Wolpe et aL., 1988;Wolpe et aL., 1989). The monocyte-derived growth factor described by Singh and Bonin (1988) is an anionic 40-kDa polypeptide.…”
Section: Introductionmentioning
confidence: 99%